Ordered arrays of nanoporous gold nanoparticles - Wang, Dong; Ji, Ran; Albrecht, Arne; Schaaf, Peter (Beilstein Journal of Nanotechnology, 2012)
A combination of a “top-down” approach (substrate-conformal imprint lithography) and two “bottom-up” approaches (dewetting and dealloying) enables fabrication of perfectly ordered 2-dimensional arrays of nanoporous gold nanoparticles. The dewetting of Au/Ag bilayers on the periodically prepatterned substrates leads to the interdiffusion of Au and Ag and the formation of an array of Au–Ag alloy nanoparticles. The array of alloy nanoparticles is transformed into an array of nanoporous gold nanoparticles by a following dealloying step. Large areas of this new type of material arrangement can be realized with this technique. In addition, this technique allows for the control of particle size, particle spacing, and ligament size (or pore size) by varying the period of the structure, total metal layer thickness, and the thickness ratio of the as-deposited bilayers.
Keywords: dealloying; dewetting; nanoimprint lithography; nanoparticles; nanoporous gold; ordered arrays